The global regulator FpLaeB is required for the regulation of growth, development, and virulence in Fusarium pseudograminearum - Wu, Yuxing; Wang, Yajiao; Han, Sen; Li, Qiusheng; Kong, Lingxiao (Frontiers in Plant Science, 2023)
Fusarium pseudograminearum is a soil-borne pathogen that is capable of causing a highly destructive crown disease in wheat. Secondary metabolite (SM) especially deoxynivalenol (DON) are the primary virulence factor during infection. Here we characterized the global regulator, FpLaeB, an ortholog of LaeB protein function to regulate the SM in Aspergillus nidulans. We found that the vegetative growth of FpLaeB deletion mutant drastically reduced compared to the wild type. FpLaeB was also important to conidiation because FpLaeB deletion mutant formed less conidia in induced medium. In addition, the sensitivity of FpLaeB deletion mutant to cell-wall integrity inhibitor was decreased, while its growth was more severely inhibited by cell membrane inhibitor SDS than that of the wild type. More importantly, the virulence was decreased when FpLaeB deletion mutant was inoculated onto wheat stem base or head. By genome-wide gene expression profiling, FpLaeB was found to regulate several processes related to above phenotype such as carbohydrate metabolic process, integral and intrinsic component of membrane, especially SM. Further, generation of DON was impaired in FpLaeB deletion mutant via UPLC-MS/MS assay. These results showed that FpLaeB plays important parts in growth, development, maintenance of cell wall and membrane integrity. More importantly, FpLaeB is required for SM and full virulence in F. pseudograminearum.